2013
DOI: 10.1017/edp.2013.14
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Practice of Psychologists in Schools in Victoria, Australia

Abstract: This article reports on a qualitative study aimed to map the professional practice of psychologists working in schools in Victoria, Australia. A review of school psychology research literature conceptualised seven domains that were used as a lens for understanding how the professional practice of psychology was enacted in schools. The domains were placed in a hierarchy to illustrate the ecological aspect of professional practice, drawing on the work of Altman (1987) and Brofenbrenner (1977). The influence of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…To illustrate, in some countries, it has been estimated that psychologists who work in schools spend approximately 50% of their time in assessment activities (Walcott & Hyson, 2018). Nonetheless, some psychologists working in school settings have expressed a desire to move beyond their role of assessor and engage in more preventative approaches (Eckersley & Deppeler, 2013).…”
Section: School Psychological Servicesmentioning
confidence: 99%
“…To illustrate, in some countries, it has been estimated that psychologists who work in schools spend approximately 50% of their time in assessment activities (Walcott & Hyson, 2018). Nonetheless, some psychologists working in school settings have expressed a desire to move beyond their role of assessor and engage in more preventative approaches (Eckersley & Deppeler, 2013).…”
Section: School Psychological Servicesmentioning
confidence: 99%
“…A position framework and practice guide for effective delivery of school-based psychology services is offered by the Australian Psychological Society (APS, 2016(APS, , 2022 to circumvent such ambiguities. However, researchers considering the degree to which aspects of the framework have been incorporated in SPC school practice have suggested that change can be slow (Thielking et al, 2018), unlikely to occur (Russell, 2019), or met with 'ambivalence' by schools (Eckersley & Deppeler, 2013). It is therefore possible that SPCs who are trying to shift to more effective whole school practices may experience stress associated with continuing role ambiguity (Culbreth et al, 2005).…”
Section: Role Ambiguitymentioning
confidence: 99%
“…Negotiating the collective and individual networks of psychoeducational reports. Existing literature often characterises the barriers that impede school psychologists' engagement with systemic and relational practice in discrete and general terms, such as widespread demand for individual assessments (Bell & McKenzie, 2013;Eckersley & Deppeler, 2013). However, the relational framework of this inquiry, and the narrative of each knowledge-making practice, suggests that while participants faced common barriers, they are not stable or structured universally across all practices.…”
Section: Translating Psychoeducational Reports: a Relational Material...mentioning
confidence: 99%